Service climate and service behavior to customer satisfaction: a multilevel study of muslim-friendly hotel - Mat Yusof, Noor Amalina; Wan Jusoh, Wan Jamaliah; Hashim, Khairusy Syakirin Has-Yun (HH Publisher, 2020)
Literature has emphasized on the importance of internal integration and external environment towards the quality of services. As Muslim-friendly hotels (MFH) are being a service organization, this research aims to integrate the organization, employee and customers who involved in the service encounters. This research purposely conducted to test the proposition that an employee’s service climate determines employee’s service behavior and consequently customer satisfaction. This cross-sectional multilevel study involved 25 MFH (n=25) with 5 employees and 5 customers for each organization, employees (n=125) and employees (n=125). The finding revealed the organizational service climate has a positive and significant impact on individual employee’s service behavior. In short, the employees at MFH acknowledge the conducive working environment which can motivate them in delivering quality service (= 0.77, SE = 0.09, p-value<0.001). The result shows that MFH has provided a motivational environment to support service delivery. However, it is insufficient to lead to customer satisfaction in relation to the inconsistent of the other hypotheses.